Relationship between Surface Electromyography Parameters and Balance Function in Patients with Lower Limb Spasm after Stroke - ZHENG Bao; LIU Yiwen; WANG Zongbao; XU Wanyue; XIONG Shanshan (康复学报)
ObjectiveTo investigate the correlation between electromyography (EMG) parameters of bilateral lower limb muscles and standing balance parameters in patients with hemiplegic lower limb spasm after stroke, and to provide basis for rehabilitation and treatment of balance function in patients with lower limb spasm after stroke.MethodsA total of 30 patients with hemiplegic lower limb spasm after stroke were recruited as the patient group from Anhui Provincial Hospital of Integrated Traditional Chinese and Western Medicine, and 30 healthy people with no history of trauma, gender, age and body mass index (BMI) matched were selected as healthy control group (referred to as healthy group). Balance function parameters such as the oscillation speed of the center of gravity, the average envelope area and the distance of the center of gravity movement track were recorded in the standing state with eyes open for 30 s. Surface EMG equipment was used to collect surface EMG signals of the vastus medialis (VM), vastus lateralis (VL), rectus femoris (RF), medial gastrocnemius (MG) and semitendinosus (SE) during maximum isometric voluntary contraction (MIVC) with passive knee flexion and extension. Then the corresponding root mean square (RMS) value and RMS symmetry index (SI) of the same muscles on both sides were calculated. Finally, Spearman correlation analysis was conducted between the calculated surface EMG parameters and various balance function parameters.ResultsThe RMS values of VM, VL, RF, MG and SE on the affected side were (126±32), (115±26), (88±35), (96±19) and (87±57) µV, respectively, which were significantly lower than those of the healthy side and the healthy group, and the differences were statistically significant (P<0.05). SI of bilateral lower limb VM, VL, RF, MG and SE in the patient group were (-0.218±0.125), (-0.285±0.168), (-0.158±0.112), (-0.255±0.120) and (-0.328±0.173), respectively, and their absolute values were significantly higher than those in the healthy group, the differences were statistically significant (P<0.05). The RMS values of RF and MG on the affected side of the patient group were positively correlated with the distance of the center of gravity movement track (rRF=0.57, P=0.02; rMG=0.51, P=0.01), the SI value measured in the patient group was positively correlated with the distance of the center of gravity movement track (rVM=0.550, P=0.011; rVL=0.561, P=0.027; rRF=0.631, P=0.017; rMG=0.665, P=0.018; rSE=0.621, P=0.024).ConclusionThe bilateral lower extremity muscle groups of patients with lower limb spasm after stroke are unbalanced. The muscle status and balance function of patients can be evaluated with the aid of surface EMG and balance assessment equipment. RMS value of affected side muscles and RMS symmetry index of bilateral lower extremity muscles can indirectly reflect the balance function of patients. SI is more valuable in predicting balance function in patients with lower limb spasm after stroke.